Gastrointestinal Stromal Tumor of the Duodenum in a 13-Year-Old Girl: A Rare Case Report - Rahmandita, Yushafira Putri; Hartiastuti, Setya Mithra (Pediatric Sciences Journal, 2024)
Introduction: One of the main causes of death for kids and teenagers is a tumor which exceeds 200.000 in all of the world. One of the tumors is Gastro Intestinal Stromal Tumor (GIST). GIST is a mesenchymal gastrointestinal tumor with a focus on the Interstitial Cells of Cajal (ICC). Not more than 100 cases of pediatric GIST and less than 5% of childhood tumors are seen in the Gastrointestinal (GI) Tract. Due to their rarity, the current literature consists only of reviews of small case series, less than a third of all cases reported in the literature. Case Description: A thirteen-year-old girl presented to the emergency room with nausea, dizziness, and syncope a day before. She had the same complaint 2 months before and was diagnosed with iron deficiency anemia but it got worse when she came to emergency in the next two months. She got some tests and found a tubulovillous adenoma suspected as GIST in duodenal. This girl was unable to survive in the intensive unit after the surgical resection due to the massive bleeding in her stomach. Conclusion:  We reported a rare case of Gastrointestinal Stromal Tumor (GIST) of the duodenum found in a girl.